2023
DOI: 10.1111/ijd.16613
|View full text |Cite
|
Sign up to set email alerts
|

Viral co‐infections in leprosy: a scoping review

Abstract: ContextThe most reported viral co-infections in leprosy are human immunodeficiency virus (HIV), human T-cell lymphotropic virus (HTLV), hepatitis B virus (HBV), hepatitis C virus (HCV), and SARS-CoV-2. In co-infections, the burden of an agent can be increased or decreased by the presence of others. To address this issue, we need to fully understand their prevalence, risk factors, immunology, clinical manifestations, and treatment. The purpose of this scoping review is to describe the clinical and epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
2
1
Order By: Relevance
“…The prevalence rates of hepatitis B and hepatitis C in leprosy patients are higher than in the general population [36]. In our study, the prevalence of hepatitis B and hepatitis C was 2.5% and 4.1%, respectively, while in Spain, the prevalence of hepatitis C was 0.2% and hepatitis B was 0.1% [37,38] and vaccination was implemented in 1994 for all newborns.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The prevalence rates of hepatitis B and hepatitis C in leprosy patients are higher than in the general population [36]. In our study, the prevalence of hepatitis B and hepatitis C was 2.5% and 4.1%, respectively, while in Spain, the prevalence of hepatitis C was 0.2% and hepatitis B was 0.1% [37,38] and vaccination was implemented in 1994 for all newborns.…”
Section: Discussioncontrasting
confidence: 44%
“…Each prevalence was lower than in leprosy patients. A recent meta-analysis also found that these co-infections were associated with higher rates of leprosy reactions [36]; unfortunately, we were unable to make this comparison in our study. Additionally, we observed a slight increase in hepatitis B co-infections and neuropathy in patients with leprosy.…”
Section: Discussionmentioning
confidence: 56%
“…Disseminated strongyloidiasis can also occur in patients with AIDS, although less frequently than in those with HTLV [ 83 ]. Because both HIV and HTLV are known to affect leprosy patients more frequently than the general population [ 84 ], we recommend that all newly diagnosed leprosy patients undergo routine stool examinations, and that prophylactic treatment with Ivermectin, at a dose of 200 μg/kg/day for 2 days, be administered to all patients beginning corticosteroid therapy, with repeat doses given after 2 weeks [ 85 ].…”
Section: Discussionmentioning
confidence: 99%